2014
DOI: 10.1021/bm401708m
|View full text |Cite
|
Sign up to set email alerts
|

Saponins: A Renewable and Biodegradable Surfactant From Its Microwave-Assisted Extraction to the Synthesis of Monodisperse Lattices

Abstract: Synthetic surfactants are widely used in emulsion polymerization, but it is increasingly desirable to replace them with naturally derived molecules with a reduced environmental burden. This study demonstrates the use of saponins as biodegradable and renewable surfactants for emulsion polymerization. This chemical has been extracted from soapnuts by microwave assisted extraction and characterized in terms of surfactant properties prior to emulsion polymerization. The results in terms of particle size distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The FTIR results (Fig. 1) clearly indicated that the extract was saponin which is comparable with other researchers [15,16,25].…”
Section: Saponin Yield and Critical Micellar Concentrationsupporting
confidence: 88%
See 1 more Smart Citation
“…The FTIR results (Fig. 1) clearly indicated that the extract was saponin which is comparable with other researchers [15,16,25].…”
Section: Saponin Yield and Critical Micellar Concentrationsupporting
confidence: 88%
“…Soap nut or Sapindus indicus belongs to Sapindaceae family, is widely available in Asian countries and had been used as a traditional surfactant for cleansing hair and body for several years [15,16]. An untried and cheap surfactant saponin extracted from soap nut is employed in this study substituting synthetic surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…20,27 The saponin molecules adsorb on the TiO 2 NP surface via hydrophobic interaction and impart a steric stabilization to the dispersion. Saponin is considered as a non-ionic natural surfactant and is used in cosmetics and pharmaceutical products.…”
Section: Surface Adsorption Of Dispersants On Nanoparticlesmentioning
confidence: 99%
“…The worldwide large production of surfactants was increased year by year due to the technological development, ease of preparation and important applications [12]. 12.5 million tonnes of surfactants were produced worldwide in 2006 [13] whereas 3 million tonnes were produced in Western Europe in 2007 [14] and approximately 172 thousand tonnes of nonionic surfactants were consumed in 2010 in US alone [5]. Therefore, use of synthetic surfactants in various applications leads to secondary pollution.…”
mentioning
confidence: 99%